DISIPLIN: SIKAP DAN PERILAKU TAAT - Dede Suleman (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
The leader is happy, when he sees an orderly employee at work, systematic in solving problems, listening to orders, pay attention to standards, be careful when working, respect the opinions of others, work together as a solid team, and so on. Indeed that is discipline. This research seeks to dig up information, obtain data, analyze findings, provide conclusions and suggestions. To prove this, a series of scientific methods was carried out using a quantitative approach and regression analysis. Data collection techniques using questionnaires and random samples. This finding suggests, that a person is said to be disciplined if his attitude is in accordance with his behavior. His behavior is measurable proof of discipline, and has implications for organizational goals